Extraction and Characterization of Microfibrillated Cellulose from Discarded Cotton Fibers through Catalyst Preloaded Fenton Oxidation - Xianmeng Xu; Ning Lu; Shunmin Wang; Mengqi Huang; Shenglong Qu; Feng Xuan (Advances in Materials Science and Engineering)
With rapid developments in science and technology, mankind is faced with the dual severe challenges of obtaining needed resources and protecting the environment. The need for sustainable development strategies has become a global consensus. As the most abundant biological resource on Earth, cellulose is an inexhaustible, natural, and renewable polymer. Microfibrillated cellulose (MFC) offers the advantages of abundant raw materials, high strength, and good degradability. Simultaneously, MFC prepared from natural materials has high practical significance due to its potential application in nanocomposites. In this study, we reported the preparation of MFCs from discarded cotton with short fibers by a combination of Fe2+ catalyst-preloading Fenton oxidation and a high-pressure homogenization cycle method. Lignin was removed from the discarded cotton with an acetic acid and sodium chlorite mixed solution. Then, the cotton was treated with NaOH solution to obtain cotton cellulose and oxidized using Fenton oxidation to obtain Fenton-oxidized cotton cellulose. The carboxylic acid content of the oxidized cotton cellulose was 126.87 μmol/g, and the zeta potential was −43.42 mV. Then, the Fenton-oxidized cotton cellulose was treated in a high-speed blender under a high-pressure homogenization cycle to obtain the MFC with a yield of 91.58%. Fourier transform infrared spectroscopy (FTIR) indicated that cotton cellulose was effectively oxidized by Fe2+ catalyst-preloading Fenton oxidation. The diameter of the MFC ranged from several nanometers to a few micrometers as determined by scanning electron microscopy (SEM), the crystallinity index (CrI) of the MFC was 83.52% according to X-ray diffraction (XRD), and the thermal stability of the MFC was slightly reduced compared to cotton cellulose, as seen through thermogravimetric analysis (TGA). The use of catalyst-preloading Fenton oxidation technology, based on the principles of microreactors, along with high-pressure homogenization, was a promising technique to prepare MFCs from discarded cotton.